Side effects of medications in professional opera singers’ voice: survey findings - Clarós, Pedro; Mikolajczyk, Kinga; Pujol, Astrid Clarós; Pujol, Carmen; Sabater, Juan; Clarós, Andrés (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Opera singers are classified under level I, as the elite vocal performers, being the quintessential representatives of this group. As the professional voice users, they meticulously observe any changes relevant to their health, therefore self-reported side effects should be taken under serious consideration. The aim of this study was to initiate the process of gathering general information about the most common side effects of medications taken by the opera singers. Methods: The study group consisted of 264 professional opera singers, treated in Clarós Clinic in a 35 years period, who were asked to complete a questionnaire. The response rate was 62.1% (n=164) with a male-to-female ratio being 1.27:1 (72 men and 92 women). 46 cases of adverse effects of medicines were updated and analysed. All the responses were collected between February and April 2018. Results: The mean age of our study group was 38.3 for females and 49.95 for males, with the range between 18-83 years. The vocal categories were as follows: 39 tenors, 17 baritones, 14 basses, 64 sopranos, 23 mezzo-sopranos and 5 contraltos. Patients with chronic diseases and comorbidities represented the 39.1% of the study group. The most common adverse effect reported was dryness (15.2%). The most frequent voice side effects raised by singers were clearing the throat frequently (14.63%), hoarseness and coarse or scratchy sound (10.37%), and vocal fatigue (7.32%). Conclusions: We believe that exploring the subject of vocal side effects of medications in professional opera singers is extremely important.